Frequency Domain Analysis of Load Frequency Control Using PIDTune Model Standard - Heru Dibyo Laksono; Rohadatul ‘Aisya; Wira Hidayat bin Mohd Saad (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2023)
The load frequency control system aims to regulate the frequency in the electric power system at a normal value with a predetermined tolerance limit. In practice, the load frequency control system does not always operate optimally, therefore a controller is needed to be added to the load frequency control system. The controller designed is a variation of the combination of Proportional-Integral-Differential (PID) controllers with the standard model PIDTune method consisting of proportional (P) controller, proportional integral (PI) controller, proportional differential (PD) controller, Proportional Integral Differential (PID) controller, Proportional Differential controller with first-order filter on differential section (PDF), and Proportional Integral Differential controller with first-order filter on differential section (PIDF). This study is aiming to carry out simulation and analysis in the frequency domain and then analyze the robustness of the reheat type power frequency control system and then design a PID controller for the reheat type power frequency control system in basic configuration, filter configuration, feedback configuration, feedforward configuration, and cascade configuration using PIDtune Model Standard on Matlab software. From the results of simulation and analysis, the controller that complies the design criteria and can make the reheat type of load frequency control system work optimally based on frequency domain analysis and robustness analysis is a proportional-integral (PI) controller in a feedback configuration with gain margin (Kg) equals to 38.11 dB, phase margin equals to 59.6°, infinity bandwidth, peak resonance value (Mr) equals to 1.19, maximum sensitivity peak value (MS) equals to 1.24, and complementary maximum sensitivity peak value (MT) equals to 1.17.